Mycotic abdominal aortic aneurysm due to streptococcus suis: A case report - Kamphol Laohapensang (2018)
Background: Streptococcus suis is a common infection of pigs. Human infection is often related to accidental inoculation through skin injuries during occupational exposure to pigs and pork. The disease may present as meningitis, bacteremia, and less commonly endocarditis, arthritis, or bronchopneumonia. Methods: Case report and review of the literature. Results: We report a case of bacteremia and severe sepsis caused by S. suis serotype 2 complicated by septic arthritis in a 56-year-old male with history of a prior contact with unprocessed pork. The causative agent was isolated from blood cultures and aspirated synovial fluid. The patient's condition improved after treatment with penicillin, but he was found subsequently to have an abdominal aortic aneurysm, confirmed by computed tomography (CT) scan. The mycotic aneurysm was successfully repaired using an in situ graft reconstruction. Tissue samples analyzed using polymerase chain reaction identified S. suis serotype 2 as the causative organism. After completion of two weeks of parenteral antibiotics, an oral form of ciprofloxacin (0.25 g twice a day) was continued for one month. The patient was discharged from our institution after uncomplicated recovery. Clinical review, a CT scan, and inflammatory markers nine months after surgery revealed no evidence of infection. Conclusion: This is the first report of mycotic aneurysm caused by S. suis, which may be an etiologic agent of mycotic aneurysms, especially when complicated by bacteremia in adults with a recent history of contact with pigs or unprocessed pork. © Mary Ann Liebert, Inc.